2006
DOI: 10.1016/j.gca.2005.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Microscale controls on the fate of contaminant uranium in the vadose zone, Hanford Site, Washington

Abstract: An alkaline brine containing uranyl (UO 2 2+ ) leaked to the thick unsaturated zone at the Hanford Site. We examined samples from this zone at microscopic scale to determine the mode of uranium occurrence-microprecipitates of uranyl (UO 2 2+ ) silicate within lithic-clast microfractures-and constructed a conceptual model for its emplacement, which we tested using a model of reactive diffusion at that scale. The study was driven by the need to understand the heterogeneous distribution of uranium and the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(107 citation statements)
references
References 49 publications
3
103
0
1
Order By: Relevance
“…The speciation of the uranium sequestered in the shallow BY Crib sediments has not been characterized to date, but is likely a relatively insoluble co-precipitate with other components in the waste stream and with secondary minerals formed when the liquid wastes interacted with the native Hanford formation sediments. Similar sequestering reactions between uranium in Hanford wastes and Hanford formation sediments have been identified (see Catalano et al 2004;Ilton et al 2008;Liu et al 2004 andMcKinley et al 2006;Qafoku et al 2005;Reeder et al 2000Reeder et al , 2001Wang et al 2005;Zachara et al 2007a,b;and Wan et al 2009). …”
Section: By and B-57 Cribssupporting
confidence: 55%
See 1 more Smart Citation
“…The speciation of the uranium sequestered in the shallow BY Crib sediments has not been characterized to date, but is likely a relatively insoluble co-precipitate with other components in the waste stream and with secondary minerals formed when the liquid wastes interacted with the native Hanford formation sediments. Similar sequestering reactions between uranium in Hanford wastes and Hanford formation sediments have been identified (see Catalano et al 2004;Ilton et al 2008;Liu et al 2004 andMcKinley et al 2006;Qafoku et al 2005;Reeder et al 2000Reeder et al , 2001Wang et al 2005;Zachara et al 2007a,b;and Wan et al 2009). …”
Section: By and B-57 Cribssupporting
confidence: 55%
“…A significant portion of the uranium present in the vadose zone sediments surrounding Tank BX-102 is found as discrete uranium precipitates such as alkali and alkaline-earth uranyl silicates and coprecipitates (Catalano et al 2004;Ilton et al 2008;Liu et al 2004 andMcKinley et al 2006;Reeder et al 2000Reeder et al , 2001Wang et al 2005;Zachara et al 2007a,b;and Wan et al 2009). These discrete uranium solid phases dissolve relatively slowly when waters with lower dissolved uranium, sodium, calcium, sulfate, and carbonate flow by the precipitated solids.…”
Section: K D Values and Ranges (By Geologic Layer)mentioning
confidence: 99%
“…These minerals are important in controlling the mobility of uranium in the contaminated subsurface. For example, the uranyl silicate, boltwoodite, and the uranyl phosphate, metatorbernite, have formed in contaminated sediments of the Hanford site [2][3][4], uranyl phosphates occur in contaminated soils of the Fernald site [5], and uranyl sulfates are common in altered mine tailings [6]. The interactions of these minerals with aqueous systems, and the details of how they dissolve and precipitate, are integral to understanding and predicting the mobility of uranium.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the results from the sub-sample measurements may contain a possible bias toward higher concentrations for some analytes that would be preferentially associated with the smallersized sediment fractions. As an example of this potential bias, we acknowledge previous investigations that reported that contaminant uranium is manifested as micro-precipitates in fractures within granitic lithic fragments that make up only 4% by volume of the Hanford sediments McKinley et al 2006). It is our contention that the contaminant uranium is not solely harbored by crevasses in lithic fragments, and our study aims to identify these additional reservoirs of uranium.…”
Section: Methodsmentioning
confidence: 92%
“…An example of a phase containing essential uranium is micro-precipitates of uranyl phosphates or silicates that precipitate in tiny cracks or void spaces within the sediments. Evidence for the existence of micro-precipitates of uranium that form in small cracks within lithic fragments has been reported in Liu et al (2004Liu et al ( , 2006 and McKinley et al (2006). These precipitates appear to be mainly uranyl [i.e., U(VI)] silicates such as boltwoodite and uranophane (Ilton et al 2006) and, by virtue of their presence in small cracks and pits, are not typically in communication with pore waters.…”
Section: Tier II Testing Of Sediments From the 241-bx Tank Farmmentioning
confidence: 99%